‘I Looked and Beheld a Country’: Home Movies, Homesteads and the Family Archive - Daniel Clayton Rathbone (Janeway JS, 2020)
Home movies, like family photographs, are important parts of family life, acting as ways to frame the idea of the family and connect different, inter-generational memories together. Footage of key moments helps develop a family identity, as well as locate it within broader historical contexts. As a result, home movies provide an incredibly useful source with which to examine the intersections between narratives of the family, nation and belonging. Utilising a collection of personal home movies, this paper will explore how these themes are touched on within the context of British Colonial Southern Africa. These films explore how ideas of family identity are rooted within ideas of home and belonging, articulating a conceptualisation of colonial Southern Africa as a ‘home-scape’ for descendant of British settlers living there during the 1950s and 1960s. These home movies draw attention to the creation of the idea of home and family, while also producing disruptive elements to those narratives.
Keywords: Psychoanalysis; gender